Organ Donation After Circulatory Death and Before Death: Ethical Questions and Nursing Implications. (August 2019) - de Tantillo, Lila; González, Juan M.; Ortega, Johis
Scientific advances have enabled thousands of individuals to extend their lives through organ donation. Yet, shortfalls of available organs persist, and individuals in the United States die daily before they receive what might have been lifesaving organs. For years, the legal foundation of organ donation in the United States has been known as the Dead Donor Rule, requiring death to be defined for organ donation purposes by either a cardiac standard (termination of the heartbeat) or a neurological one (cessation of all brain function). In this context, one solution used by an increasing number of health care facilities since 2006 is donation after circulatory death, generally defined as when care is withdrawn from individuals who have known residual brain function. Despite its increased use, donation after circulatory death remains ethically controversial. In addition, some ethicists have advocated forgoing the Dead Donor Rule altogether and allowing donation before or near death in certain circumstances. However, nurses and other health professionals must carefully consider the practical and ethical implications of broadening the Dead Donor Rule—as may be already occurring—or removing it entirely. Such changes could harm both the integrity of the health care system as well as efforts to secure organ donation commitments from the public and are outweighed by the moral and pragmatic cost. Nurses should be prepared to confront the challenge posed by the ongoing scarcity of organs and advocate for ethical alternatives including research on effective care pathways and education regarding organ donation.